2015
DOI: 10.1109/tap.2015.2422353
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Performance of Off-Body MB-OFDM UWB-MIMO

Abstract: Abstract-This paper introduces a novel formalism to improve the performance of an off-body system by deploying multiple Ultra Wide Band (UWB) antennas, positioned strategically on the body. A methodology is presented for determining the optimal positions of UWB antennas on the body, necessary to provide a reliable Mult-Band Orthogonal Frequency Division Multiplexing (MB-OFDM) UWB diversity antenna system operating in the Federal Communications Commission frequency band between 3.1 and 10.6 GHz. By evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…These localization techniques can be influenced due to the correlation between receivers [18]. In the literature, many research works devoted to study the diversity performance of off-body systems can be found [19]. However, to the best of the authors' knowledge, not many studies about the UWB in-body channel diversity considering experimental scenarios are addressed in literature.…”
mentioning
confidence: 99%
“…These localization techniques can be influenced due to the correlation between receivers [18]. In the literature, many research works devoted to study the diversity performance of off-body systems can be found [19]. However, to the best of the authors' knowledge, not many studies about the UWB in-body channel diversity considering experimental scenarios are addressed in literature.…”
mentioning
confidence: 99%
“…However, the frequency range (3.1-10.6 GHz) is commonly used [3] and [4]. (5) [6] and IEEE 802.15.6 for WBANs [7], and [8].…”
Section: Overview Of Uwbmentioning
confidence: 99%
“…Measurement conducted in [4] showed that using multiple-input, multiple output antennas drastically improves the reliability of the off-body link. A methodology for determining the optimal positions of these antennas, independent of frequency or communication standard used, was presented in [5].…”
Section: Introductionmentioning
confidence: 99%
“…The performance improvement methods presented in for example, [3][4][5], rely on good understanding of the propagation channel characteristics. An empirical characterization of offbody wireless channels is presented in [6].…”
Section: Introductionmentioning
confidence: 99%